(untitled) - Burkhardt, V.R. (New York, 1997)
An encyclopaedic account of traditional Chinese festivals, customs and beliefs, lavishly illustrated with line drawings and paintings, this remarkable work by an Englishman who spent twenty years in China from the Imperial aftermath through the establishment of Communism, gives fascinating insights into a complex culture poised between past and present. Burckhardt's beautifully written and detailed work includes the rites practiced by the Manchu royal court and the rituals permitted under the Communist and Nationalist regimes, the festivals of working people and villagers as well as the ceremonies of the mandarins of Peking and Hong Kong, in all seasons of the year. He was especially close to the renowned Boat People of the former colony, and gives a unique account of life abroad the harbour junks and their sea-borne celebrations. Among the subjects dealt with are Chinese cuisine, the meaning of presents, secret societies, the Chinese calendar, cats (the Chinese prefer cats with yellow eyes), Chinese dress, jade carving, feng shui, etiquette, the hundreds of gods of house and wayside, temples and their guardians, and all the great festivals -- those of the Moon, the Dragon Boats, the Hungry Ghosts, the Magnolia, the New Year and many more. Chinese creeds and customs were Burkhardt's passion, and no better account of them will ever be written. Contains all three original volumes
Keywords: China; Social life and customs; 1949-